2020
DOI: 10.1002/pbc.28272
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of osteopontin from birth to adulthood

Abstract: Aim: Osteopontin (OPN) has been investigated as a biomarker for cancer and nonmalignant diseases during the last decades. Data about OPN as a potential biomarker in childhood diseases are still sparse, and reference values are not available in children. We aimed to establish reference values for children from birth to young adulthood and evaluate whether there are age-, gender-, and weight-specific differences. Method:Umbilical cord blood and blood plasma samples of 117 children were collected in the Children'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
(119 reference statements)
2
7
0
Order By: Relevance
“…In our study, mean OPN plasma concentrations in cord blood and in mothers at delivery were 332 ng/mL and 73 ng/mL respectively, concentrations comparable to studies performed in non-endemic countries [ 44 , 47 49 ]. Similar to our results, previous reports have presented increased mean OPN concentrations in infants compared to adults [ 44 , 48 , 50 ] and no significant difference between pregnant and non-pregnant women [ 47 , 48 ]. A prospective study aiming to establish OPN reference values in different age groups in Germany, demonstrated that OPN values in plasma were age dependent [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, mean OPN plasma concentrations in cord blood and in mothers at delivery were 332 ng/mL and 73 ng/mL respectively, concentrations comparable to studies performed in non-endemic countries [ 44 , 47 49 ]. Similar to our results, previous reports have presented increased mean OPN concentrations in infants compared to adults [ 44 , 48 , 50 ] and no significant difference between pregnant and non-pregnant women [ 47 , 48 ]. A prospective study aiming to establish OPN reference values in different age groups in Germany, demonstrated that OPN values in plasma were age dependent [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our results, previous reports have presented increased mean OPN concentrations in infants compared to adults [ 44 , 48 , 50 ] and no significant difference between pregnant and non-pregnant women [ 47 , 48 ]. A prospective study aiming to establish OPN reference values in different age groups in Germany, demonstrated that OPN values in plasma were age dependent [ 50 ]. However, the mean OPN plasma concentration in cord blood and in adults were markedly higher (2300 ± 552 ng/mL and 330 ng/mL) compared to our results.…”
Section: Discussionsupporting
confidence: 92%
“…Osteopontin, an inhibitor of CaOx stone formation, has been reported to modify CaOx crystallisation kinetics towards the formation of COD rather than COM [ 25 ]. Decreasing blood levels of osteopontin with age could favour higher COD proportions with increasing age [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] In agreement with our data, human plasma SPP1 was recently found to have a constant age‐related decline from birth until the age of 14 years with the highest levels between 0 and 24 months of age. [ 22 ] Cluster 3, which included an increase in protein levels between 12 and 24 months, included proteins that may be induced by the immune stimulation associated with entering preschool, in Sweden usually at 1.5 years of age, as exemplified by TNF. [ 23 ] The costimulatory protein CD40, required for activating antigen‐presenting cells, [ 24 ] showed a cluster 4 profile, which may illustrate a successively maturing immune system.…”
Section: Discussionmentioning
confidence: 99%